Managing marine fishery in Kerala through simulation using surplus production model, genetic algorithm and spectral methods - Sathianandan, T V; Jayasnakar, J (Indian Journal of Fisheries, 2016)
Outboard ring seines and mechanized trawl nets form the two major fisheries in Kerala accounting for about 72% of the totalcatch in the state. A genetic algorithm was developed for simulation of trawl net and ring seine fishery using surplus productionmodel and spectral methods. Simulations were carried out for six different levels of exploitations and the average biomassand average yield were calculated and compared with the maximum sustainable yield (MSY). The simulation results basedon ring seine fishery revealed that the optimum level of exploitation is at 86.3% of the current level of exploitation to keepthe annual average yields during 2005-2014 just below MSY, for both oil sardine and mackerel. Simulations based on trawlnet fishery suggested maintaining the exploitation level at 87.9% of the current level to retain the average annual yields ofpenaeid prawns, cephalopods and threadfin breams below the MSY level during 2005-2013.